If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(m + -4) = 6(m + -4) Reorder the terms: -3(-4 + m) = 6(m + -4) (-4 * -3 + m * -3) = 6(m + -4) (12 + -3m) = 6(m + -4) Reorder the terms: 12 + -3m = 6(-4 + m) 12 + -3m = (-4 * 6 + m * 6) 12 + -3m = (-24 + 6m) Solving 12 + -3m = -24 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 12 + -3m + -6m = -24 + 6m + -6m Combine like terms: -3m + -6m = -9m 12 + -9m = -24 + 6m + -6m Combine like terms: 6m + -6m = 0 12 + -9m = -24 + 0 12 + -9m = -24 Add '-12' to each side of the equation. 12 + -12 + -9m = -24 + -12 Combine like terms: 12 + -12 = 0 0 + -9m = -24 + -12 -9m = -24 + -12 Combine like terms: -24 + -12 = -36 -9m = -36 Divide each side by '-9'. m = 4 Simplifying m = 4
| 0.5(11.8-173.8)=-1(-173.8)-81 | | 196x^2-1=0 | | 20=3-9a | | 8-x=98 | | 5=11-3f | | -4+10x=15 | | 12-3k=6 | | 8-2x=-20 | | -8(x-8)=8(-7x+8)+6x | | 0.5(11.8-x)=-1x-81 | | 2=-3x^2-3x | | 8-5x=-3x+14 | | -2(7p-2)=-5(p+1) | | 6x-18=-(3x+2)+6 | | y=sin^2(3x^5) | | 1/4(9-5x)=-x | | 3x-2.4=x | | 6g-3/5=14 | | 3/5x+5=2/3x+3 | | 4(f-3)+34=2f+3(2f+2) | | 6+2p-1=7p+17-3p | | -2(n-2)-8=-4-2n | | (300/x)+10+.03x=0 | | 300/x+10+.03x=0 | | 5+8(v-1)=25+4v | | (17)4+(5)12x=(11)(18-5x) | | 3x+4=2(3x) | | 16x^2+1=8x | | -.5c=2.5 | | -5-(1+6m)=2-7n | | t-6=35 | | -6x+15y=-15 |